LANDASAN FILOSOFIS PERILAKU KONSUMEN DALAM PERSPEKTIF EKONOMI ISLAM DAN KONVENSIONAL (Mazahib, 2012)
The foundation of consumer behavior of different Muslim conventional consumer behavior. Conventional consumer behavior put self-interest and utilitarianism that aims to maximize satisfaction with the philosophical basis of rational economic man, positivism, and the laws say. Moderate Muslim consumer behavior based on Islamic philosophy of man. Islamic concept of man as a servant of God put man in charge of worship and as khalifatullah to carry the mandate to implement activities to prosper (Imarah) earth as a worldly activity. This balance reflects a fundamental principle in Islam. So in an Islamic perspective of consumption activities that are part of worldly activity is part of the duty of a Muslim as a whole the same position with religious activity. There is no separation between the worldly and hereafter, between economics and religion.